ChemInform Abstract: Complementary Regioselectivity in Rh(III)‐Catalyzed Insertions of Potassium Vinyltrifluoroborate via C—H Activation: Preparation and Use of 4‐Trifluoroboratotetrahydroisoquinolones. Issue 34 (1st August 2013) - Presset, Marc; Oehlrich, Daniel; Rombouts, Frederik; Molander, Gary A.
Abstract The Rh(III)‐catalyzed annulations of benzhydroxamates with potassium vinyltrifluoroborate proceed with high regioselectivity in most of the cases and in a fashion that is regiocomplementary to that of most terminal alkenes.